Serum biomarkers as personalised medicine for diagnostic and therapeutic approaches of hepatocellular carcinoma - Bakhtiar, M. Taher; Muhamad Asri, Muhamad Aqil Ikram; Abdul Rahman, Nur Damia; Zamzuri, Nur Eleisha; Muhammad Faizal, Nur Syazwani; Khotib, Junaidi; Darnis, Deny Susanti; Hasdan, Nurul Athirah; Haris, Muhammad Salahuddin; Rakhmawati, Rita (Springer Science and Business Media Deutschland GmbH, 2026)
Hepatocellular carcinoma (HCC) is a critical public health concern due to its rising incidence and mortality. Early diagnosis is challenging due to nonspecific symptoms and limitations of traditional methods. This study explores the potential of three key biomarkers, serum alpha-fetoprotein (AFP), des-γ-carboxyprothrombin (DCP), and glypican-3 (GPC3), in advancing personalized medicine for HCC, focusing on their roles in diagnostics and therapeutics. We conducted a literature review using specific keywords to narrow our search. Our findings indicate that AFP and DCP are primarily used for diagnostics, while GPC3 serves both diagnostic and therapeutic purposes. AFP is commonly used in late-stage detection due to its limited sensitivity and specificity in early stages, which can lead to false diagnoses. DCP plays a significant role as both a diagnostic tool and therapeutic target, while GPC3 is used to differentiate malignant from non-cancerous liver tissues. The review highlights the mechanisms, roles, and personalised treatments associated with these biomarkers, while also addressing challenges such as biopsy issues and funding limitations. In conclusion, the development and improvement of AFP, DCP, and GPC3 as biomarkers for the diagnostics and treatment of HCC are important. Thus, their limitations should be addressed as these biomarkers play a crucial role in modern cancer therapy and are critical for increasing the survival rates of HCC patients.